Pregnancy of unknown location: outcome in a tertiary care teaching hospital - Sri, A. Shanti; Kalpana, P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: A pregnancy of unknown location (PUL) is a descriptive term used to classify a woman when she has a positive pregnancy test but no intra- or extra-uterine pregnancy is visualized on transvaginal sonography. The objective of present study was to find out the outcome of women with pregnancy of unknown location presenting to a tertiary care teaching hospital. Methods: The prospective study was conducted from from 1st October 2015 to 31st September 2016, to antenatal out-patient department, at Princess Esra Hospital, Deccan College of medical sciences, Hyderabad. Data was collected for women with early pregnancy or with history of amenorrhea, bleeding or pain. These women were investigated with serum beta-human chorionic gonadotrophin levels at interval of 48 hrs and transvaginal ultrasonography. Expectant management was done for failing pregnancy of unknown location while medical or surgical management was considered for persistent pregnancy of unknown location and ectopic pregnancy. Results: During study period, 9210 patients were admitted, and, of them, 960 (10.42%) were patients with early pregnancy. Meeting the inclusion criteria were 112 (11.6%) patients who formed the study sample. There were 104 (92.85%) patients presenting with amenorrhea, 98 (87.5%) had bleeding and 78 (69.64%) presented with pain. Outcome of 42 (48.83%) patients was failing pregnancy, 31 (36.04%) had intrauterine pregnancy, 8 (9.3%) converted to ectopic pregnancy, while 5 (5.81%) had persistent pregnancy of unknown location. All patients with persistent pregnancy of unknown location and 3 patients with ectopic pregnancy were medically treated. Three patients having an ectopic pregnancy were managed surgically. Conclusions: Management of choice for asymptomatic patients having pregnancy of unknown location is expectant management. Most of the patients suspected to have PUL resolved either into F-PUL or IUP with expectant management.